1997
DOI: 10.1111/j.1600-0722.1997.tb00201.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulp calcifications in traumatized primary incisors A morphological and inductive analysis study

Abstract: The purpose of this study was to investigate histopathological changes in primary teeth following trauma, and to look for possible correlations between the morphology of pulpal calcification and clinical findings. The material consisted of 123 primary teeth from 98 Danish children aged 9-108 months (mean age 33.5 +/- 19.7 months) at the time of injury. The specimens were analyzed by means of light and scanning and transmission electron microscopy. Data from the clinical investigation and from predetermined ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
38
1
5

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 11 publications
5
38
1
5
Order By: Relevance
“…This finding significantly expanded our expectations to explain the formation of dental pulp calcification, of which the etiology until now was ambiguous. [19][20][21][22] As far as we know today, pulp calcification is a type of chronic regressive degeneration of the pulp tissue; however, what leads to this devolution remains unclear. Dystrophic calcification is found to be of a variable degree, and this might originate from the impairment of the host cells.…”
Section: Introductionmentioning
confidence: 99%
“…This finding significantly expanded our expectations to explain the formation of dental pulp calcification, of which the etiology until now was ambiguous. [19][20][21][22] As far as we know today, pulp calcification is a type of chronic regressive degeneration of the pulp tissue; however, what leads to this devolution remains unclear. Dystrophic calcification is found to be of a variable degree, and this might originate from the impairment of the host cells.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the formation of mineralized tissue within the pulp cavity has been widely examined in both clinical and animal studies. These studies ordinarily focused on the formation of reparative dentin and the dentin bridge, although several other reports described the induction of bone-like tissues in the pulp cavity following various stimulations such as tooth transplantation (Hosoya et al 2003) or replantation (Zhao et al 2007;Mutoh et al 2011), traumatic injury (Robertson et al 1997), and laser irradiation (Tate et al 2006). These bone-like tissues are quite similar to normal bone regarding their histological appearance and matrix properties; however, the origin of the osteoblast-like cells that appear in the dental pulp is still controversial.…”
mentioning
confidence: 99%
“…Robertson et al reported that tissues that block the pulp chamber exhibit reparative reactions by dentin-like, bone-like, or fibrous tissues 22) . They also reported pulp necrosis due to root canal obstruction after trauma in 8.5% of teeth, noting that this percentage increased with time 23) .…”
Section: Calcified Tissue In Pulp Chambermentioning
confidence: 99%